Laparoscopic surgery in pediatric upper tract urolithiasis: An alternate modality - Chhabi Ranu Gupta (Wolters Kluwer Medknow Publications, 2021)
Introduction: Incidence of pediatric urolithiasis has increased over the last few decades. Procedures such as extracorporeal short wave lithotripsy, percutaneous nephrolithotripsy, and ureterorenoscopic lithotripsy are not widely available for pediatric age group in many developing countries. It is desirable that advantages of minimally invasive surgery be offered to selected cases with urolithiasis. Materials and Methods: All patients with pediatric upper tract urolithiasis managed laparoscopically from January 2015 to April 2020 were retrospectively reviewed. Results: A total of 38 patients were included. The mean age of the patients was 8 ± 2.85 years. Thirty-four patients (renal and upper ureteric) were managed through retroperitoneal approach, while those with lower ureteric calculi (n = 4) were approached transperitoneally. A total of eight patients required conversion to open technique. The stone clearance rate was 79% by laparoscopic approach alone. There were no procedure-related complications. Conclusion: Our study suggests that laparoscopic management for pediatric upper tract urolithiasis is a radiation-free, single-time curative treatment and is feasible in centers where facilities for other endoscopic procedures are unavailable.